Effects of Axivity 3.0-based management model on pregnant women with gestational diabetes mellitus - Cai, Fengcheng; Wu, Yingying; Liu, Bei; Xu, Mengyan (Frontiers in Endocrinology, 2026)
AimsTo evaluate the effect of a precision exercise management model based on the Axivity 3.0 device on physical activity levels, glucose control, and delivery outcomes in patients with gestational diabetes mellitus (GDM).Patients and methodsThis study employed a randomized controlled design. One hundred patients with GDM from Hangzhou Women’s Hospital from May 2020 to September 2020 who received regular obstetric follow-ups and intended to deliver in our hospital were recruited. Patients were randomly divided into a control group (conventional health education model of exercise during pregnancy) and a test group (received the Axivity 3.0-based management model combined with health education). A general information questionnaire, Pregnancy Exercise Self-efficacy Scale (P-ESES), Pregnancy Physical Activity Questionnaire; physical activity levels; fasting blood glucose (FBG), 2-hour postprandial blood glucose (2hPG); the duration of the first and second stages of labor for vaginally-delivering patients were assessed.ResultsAfter the 4-week intervention, the total P-ESES score was significantly higher in the test group (median 39, IQR 36-42) than in the control group (median 36, IQR 33-38; p < 0.001). Weekly moderate-to-vigorous physical activity (MVPA) time increased to 75.95 ± 28.30 minutes in the test group versus 56.24 ± 23.66 minutes in the control group (mean difference: 19.71 minutes/week, p=0.001). At delivery, fasting blood glucose (FBG) and 2-hour postprandial glucose (2hPG) levels were significantly lower in the test group (FBG: 4.47 ± 0.47 mmol/L; 2hPG: 5.40 ± 0.56 mmol/L) compared to the control group (FBG: 4.82 ± 0.41 mmol/L, p=0.001; 2hPG: 6.02 ± 0.63 mmol/L, p<0.001). Total gestational weight gain was lower in the test group (11.95 ± 4.89 kg) than in the control group (14.32 ± 4.80 kg, p=0.030). Among vaginally-delivering patients, the median duration of the first and second stages of labor was shorter in the test group (389.5 and 44.5 minutes, respectively) than in the control group (510.0 and 51.0 minutes, respectively; p=0.015 and p=0.033).ConclusionThe Axivity 3.0-based precision management model was associated with significant improvements in exercise self-efficacy, increased moderate-to-vigorous physical activity, and better glycemic control and weight management in patients with GDM compared to conventional health education alone.Summary pointsAfter the 4-week intervention, the test group showed a significantly higher total Pregnancy Exercise Self-Efficacy Scale (P-ESES) score (median 39 vs. 36 in controls, p < 0.001) and achieved greater weekly moderate-to-vigorous physical activity (MVPA) time (75.95 vs. 56.24 minutes, p=0.001). At delivery, fasting blood glucose (FBG: 4.47 vs. 4.82 mmol/L, p=0.001) and 2-hour postprandial glucose (2hPG: 5.40 vs. 6.02 mmol/L, p<0.001) levels were significantly lower in the test group compared to the control group. Total gestational weight gain was better controlled in the test group (11.95 kg) than in the control group (14.32 kg, p=0.030). Among vaginally-delivering patients, the median duration of the first stage (389.5 vs. 510.0 minutes, p=0.015) and the second stage (44.5 vs. 51.0 minutes, p=0.033) of labor was significantly shorter in the test group. The Axivity 3.0-based management model helps improve pregnancy exercise self-efficacy, elevate exercise time, and control blood glucose levels and weight gain in patients with GDM.